Spine tuberculosis:The greatest mimicker - Subramaniam, Kishan Rao; Komahen, Colin; Mor Japar Khan, Ed Simor Khan (2018)
INTRODUCTION: Spinal tuberculosis is a destructive form of tuberculosis. Common clinical manifestations are often vague and may mimic other medical conditions. We are presenting a case report of a lady who initially presented with clinical presentation suggestive of spine metastasis, however intraoperative and post operative findings turned out to be spine tuberculosis. This patient benefitted from early surgical decompression and drainage with rapid recovery of her neurology. CASE REPORT: 68 years old lady presented with back pain with bilateral lower limb weakness and numbness for the past 2 weeks with bowel and bladder incontinence. She denied any TB contact and has no family history of malignancy. On examination, patient has a thyroid swelling. She was paraplegic with reduced sensation T6 downwards. Back pain was aggravated with movement. MRI film and report showed presence of intraspinal extramedullary lesion at T6-T7 with impression of cord compression with suspicious of metastasis. From the clinical presentation and investigation result, the condition was highly suspicious of spine metastasis. Tuberculosis workout done was negative. Intraoperatively noted caseous material seen from vertebral body compressing anterior aspect of the cord with pus formation. PSIF (T4-T9), laminectomy (T5-T6), transpedicular corpectomy (T6) with trapdoor osteotomy approach and mesh cage with bone grafting was done. Patient was started on anti TB medications. Post operatively, the instability pain resolved completely and improvement in neurology of the patient was noted as early as one week post-op. DISCUSSION: Spinal tuberculosis is a destructive form of tuberculosis. Common clinical manifestations are often vague and may mimic other medical conditions. For the diagnosis of spinal tuberculosis MRI is more sensitive and specific than x-ray and CT scan. However, these findings may sometimes be mistaken for spine metastasis or severe degenerative spine. Neuroimaging-guided needle biopsy is the gold standard technique for early histopathological diagnosis. Antituberculous treatment remains the cornerstone of treatment. Surgery may be required in selected cases, e.g. large abscess formation, severe kyphosis, an evolving neurological deficit, or lack of response to medical treatment. In our patient,early decompression with drainage of the collection surrounding the cord provided good results after surgery with improvement in patient’s neurology. CONCLUSION: Diagnosis of TB spine has often been a challenge to orthopedic surgeons. Its clinical presentations is often non specific and may mimic other diseases, thus the name “The Greatest Mimicker”. With early diagnosis and early treatment, prognosis is generally good.